Exploring the intersections between Information Visualization and Machine Learning - Corrêa, Igor Bueno (2018)
With todays flood of data coming from many types of sources, Machine Learning becomes increasingly important. Though, many times the use of Machine Learning is not enough to make sense of all this data. This makes visualization a very useful tool for Machine Learning practitioners and data analysts alike. Interactive visualization techniques can be very helpful by giving insight on the meaning of the output from classification tasks. In this work, the aim is to explore, implement and evaluate different visualization techniques with the explicit goal of directly relating these visualization to the Machine Learning process. The proposed approach is the development of visualization techniques for a posteriori analysis that combines data exploration and classification evaluation. Results include a modified version of the Radial Visualization technique, called Dual RadViz, and also the use of interactive multiclass Partial Dependence Plots as means of finding counterfactual explanations about Machine Learning classification. An account of some of the many ways Machine Learning and visualization are used together is also given.